MODERN TRENDS IN THE SURGICAL TREATMENT OF MASSIVE PULMONARY EMBOLISM (review of literature) - G. G. Khubulava; S. V. Sadovoi; E. K. Gavrilov (Вестник хирургии имени И.И. Грекова)
We tried to analyze current data and trends in the surgical treatment of pulmonary embolism.Surgical treatment of pulmonary embolism is a safe and effective procedure, but still is an unpopular tactic and it often remains in reserve treatment. It is necessary to conduct more large-scale studies in order to consolidate firm positions in the treatment of this cohort of patients with embolectomy, which will make it possible to further improve the prognosis and survival in patients with massive PE.